Diplomacy and diplomats in the late Portuguese Middle Ages (1431-1475) - de Babo Marinho, Duarte (2020)
Our main objective is to carry out an overall reflection on the men who formed the Portuguese royal diplomacy between 1431 and 1475. Therefore, in addition to pointing out some lines of force regarding the constituent members of the Portuguese embassies, like the composition the characteristics of diplomatic agents and the monarch's strategies for recruitment, we will seek to highlight certain issues such as the acquisition of skills and the duration of careers.   Bibliography Handwritten sources Arquivo Nacional da Torre do Tombo, Chancelaria Régia, Chancelaria de D. Afonso V, Livro 9. Biblioteca Nacional de França, Mss Lat. 6020. Biblioteca Nacional de Portugal, Maço 226. Biblioteca Pública de Évora, Fundo Manizola, Códice 177.   Printed sources ÁLVARES, Fr. João – Trautado da vida e feitos do muiito vertuoso Sr. Infante D. Fernando. in Obras de Frei João Álvares. Ed. Adelino Almeida Calado. Vol. 1. Coimbra: Imprensa da Universidade, 1959-1960. CHAVES, Álvaro Lopes de – Livro de apontamentos (1438-1489). Códice 443 da colecção Pombalina da B. N. L. Ed. Anastácia Mestrinho Salgado e Abílio José Salgado. Lisboa: Imprensa Nacional-Casa da Moeda, 1984. DUARTE, Dom – Leal Conselheiro. Ed. Maria Helena Lopes de Castro e Afonso Botelho. Lisboa: Imprensa Nacional-Casa da Moeda, 1999. DUARTE, Dom – Livro dos conselhos de el-rei D. Duarte. Livro da Cartuxa. Ed. A. H. de Oliveira Marques e João José Alves Dias. Lisboa: Editorial Estampa, 1982. LIVRO Vermelho de D. Afonso V. in Collecção de livros ineditos da Historia portuguesa dos reinados de D. Affonso V a D. João II. Ed. José Correia Serra. Vol. 3. Lisboa: Academia Real das Sciencias, 1790-1793. MONUMENTA Henricina. Ed. António Joaquim Dias Dinis. 15 vols. Coimbra: Comissão Executiva do V Centenário da Morte do Infante D. Henrique, 1960-1974. ORDENAÇÕES Afonsinas. Ed. Mário Júlio de Almeida Costa e Eduardo Borges Nunes. 2ª Ed. 5 vols. Lisboa: Fundação Calouste Gulbenkian, 1998. PORTUGUESE Abbot in Renaissance Florence. The letter collection of Gomes Eanes (1415-1463). Ed. Rita Costa Gomes. Firenze: Casa Editrice/Leo S. Olschki, 2017. ZURARA, Gomes Eanes de – Crónica da tomada de Ceuta. Ed. Reis Brasil. Lisboa: Europa-América, 1992.   Studies ARAÚJO, Julieta – Portugal e Castela na Idade Média. Lisboa: Edições Colibri, 2009. AUTRAND, Françoise – “Office et officiers royaux en France sons Charles VI (1388-1413)”. Revue Historique, 93e année, 242 (1969), pp. 49-64. AUTRAND, Françoise; CONTAMINE, Philippe – “Naissance de la France: naissance de sa diplomatie. Le Moyen Âge”. in Histoire de la diplomatie française. Du Moyen Âge à l’Empire. Vol. 1. Paris: Perrin, 2005, pp. 39-177. BECEIRO PITA, Isabel – “La consolidación del personal diplomático entre Castilla y Portugal (1392-1455)”. in III Jornadas Hispano-portuguesas de Historia Medieval. La Península Ibérica en la Era de los Descubrimientos (1391-1492). Vol. 2. Sevilla: Consejería de Cultura. Junta de Andalucía, 1997, pp. 1735-1744. BECEIRO PITA, Isabel – “La importancia de la cultura en las relaciones peninsulares (siglo XV)”. Anuario de Estudios Medievales [Em linha] 29 (1999), pp. 79-104. [Consultado a 12 julho 2018]. Disponível em https://digital.csic.es/bitstream/10261/14366/1/20090630144606228.pdf. BECEIRO PITA, Isabel – “La tendencia a la especialización de funciones en los agentes diplomáticos entre Portugal y Aragón (1412-1465)”. in El Poder Real en la Corona de Aragón. XV Congreso de Historia de la Corona de Aragón. Vol. 2. Zaragoza: Gobierno de Aragón, 1994, p. 441-455. BENNÀSSER, Pau – “Negociar la paz en el siglo XIV”. in COELHO, Maria Helena da Cruz; GOMES, Saúl António; RIBEIRO, Ângelo (ed.) – A Guerra e a sociedade na Idade Média. VI Jornadas luso-espanholas de estudos medievais. Eds. Maria Helena da Cruz Coelho, Saúl António Gomes e Ângelo Ribeiro. Vol. 2. Coimbra, 2009, pp. 16-28. BRANCO, Maria João; FARELO, Mário – “Diplomatic Relations: Portugal and the Others”. in MATTOSO, José (dir.) – The Historiography of Medieval Portugal: c. 1950-2010. Lisboa: Instituto de Estudos Medievais, 2011, pp. 231-259. CAÑAS GÁLVEZ, Francisco de Paula – “La diplomacia castellana durante el reinado de Juan II: la participación de los letrados de la cancelaría real en las embajadas regias”. Anuario de Estudios Medievales [Em linha] 40/2 (2010), pp. 691-722. [Consultado a 12 julho 2018]. Disponível em http://estudiosmedievales.revistas.csic.es/index.php/estudiosmedievales/article/view/321/325. CÓRDOVA MIRALLES, Álvaro Fernández de – “Imagen de los Reyes Católicos en la Roma pontifícia”. En la España Medieval [Em linha] 28 (2005), pp. 259-354. [Consultado a 12 julho 2018]. Disponível em https://dialnet.unirioja.es/servlet/articulo?codigo=1226611. FARELO, Mário – “La représentation de la couronne portugaise à Avignon et ses agents (1305-1377)". Anuario de Studios Medievales [Em linha] 40/2 (2005), pp. 723-763. [Consultado a 12 julho 2018]. Disponível em https://dialnet.unirioja.es/servlet/articulo?codigo=3332267. FARIA, Ana Leal de – “«Tu felix Austria nubes»”. in RODRIGUES, Ana Maria S. A; SILVA, Manuela Santos; FARIA, Ana Leal de (coord.) – Casamentos da Família Real Portuguesa. Vol. 1. Lisboa: Círculo de Leitores, 2017, pp. 57-77. FARIA, Diogo; MARIANI, Andrea – “«Todos hão de ficar cegos»: l’Italia di fine XV secolo osservata da un cardinale portoghese”. Mediterranea - ricerche storiche Ano 14 (dezembro 2017), pp. 695-706. FARIA, Diogo – “Uma embaixada portuguesa do final da Idade Média: de Lisboa a Roma, 1443-1445”. Anuario de Estudios Medievales [Em linha] 48/2 (2018), pp. 695-721. [Consultado a 9 setembro 2018]. Disponível em https://research.unl.pt/ws/portalfiles/portal/12794762/901_916_1_PB.pdf. FARIA, Diogo – “A participação de letrados laicos nas embaixadas portuguesas do final da Idade Média (1385-1495)”. in VIGIL MONTES, Néstor (dir.) - Comunicación política y diplomacia en la Baja Edad Media [Em linha]. Évora: Publicações do Cidehus, 2019 [Consultado a 1 julho 2019]. Disponível em https://books.openedition.org/cidehus/7350. FARIA, Tiago Viúla de – “Pela “Santa Garrotea”: Ofício cavaleiresco nas vésperas de Alfarrobeira”.  in Actas do XIV Colóquio de História Militar: Portugal e os conflitos militares internacionais. Vol. 2. Lisboa, 2006, pp. 61-86. FARIA, Tiago Viúla de – “Por prol e serviço do reino? O desempenho dos negociantes portugueses do Tratado de Windsor e suas consequências nas relações com Inglaterra (1384-1412)”. in Actas das VI Jornadas luso-espanholas de Estudos Medievais. A Guerra e a Sociedade na Idade Média. Vol. 2. SPEM, 2009, pp. 209-227. FARIA, Tiago Viúla de – “Tracing the ‘chemyn de Portynlage’: English Service and Servicemen in Fourteenth-Century Portugal”. Journal of Medieval History 37/3 (setembro 2011), pp. 257-268. FERREIRA, Ana Maria – “O processo de Pedro Barreto contra Jean Forestier. Um episódio nas relações luso-francesas”. Revista da Faculdade de Letras de Lisboa 1 (1977), pp. 619-639. FONSECA, Luís Adão da – O essencial sobre o Tratado de Windsor. Lisboa: Imprensa Nacional-Casa da Moeda, 1986. FONSECA, Luís Adão da – D. João II. Mem Martins: Círculo de Leitores, 2005. FREITAS, Judite de – O Estado em Portugal: (séculos XII-XVI): modernidades medievais. Lisboa: Alêtheia, 2012. GANSHOF, François – Le Moyen Age. in RENOUVIN, Pierre (dir.) – Histoire des Relations Internationales. 3ª Ed. Vol. 1. Paris: Librairie Hachette, 1964. GILLI, Patrick – “Bernard de Rosier et les débuts de la réflexion théorique sur les missions d’ambassade”. in ANDRETTA, Stefano; PÉQUIGNOT, Stéphane; WAQUET, Jean-Claude (dir.) – De l’ambassadeur. Les éscrits relatifs à l’ambassadeur et à l’art de négocier du Moyen Âge au début du XIXe siècle [Em linha].  Roma: Publications de l’École française de Rome, 2016 [Consultado a 12 julho 2018]. Disponível em https://books.openedition.org/efr/2907. GOMES, Saul António – D. Afonso V. O Africano. Mem Martins: Círculo de Leitores, 2006. HESPANHA, António Manuel – História das instituições: época medieval e moderna. Coimbra: Almedina, 1982. HOMEM, Armando Luís de Carvalho – “De João das Regras ao Conselho Régio: os legistas na afirmação da nova dinastia”. in DOMINGUES, Francisco Contente; HORTA, José da Silva; VICENTE, Paulo David (org.) – D'aquém, d'além e d'Ultramar: homenagem a António Dias Farinha. Vol. 2. Lisboa: Universidade de Lisboa. Faculdade de Letras/Centro de História, 2015, pp. 1061-1074. HOMEM, Armando Luís de Carvalho – “Diplomacia e diplomatas nos finais da Idade Média a propósito de Lourenço Anes Fogaça, chanceler-mor (1374-1399) e negociador do Tratado de Windsor”. in Actas do Colóquio Comemorativo do VI Centenário do Tratado de Windsor. Porto: Instituto de Estudos Ingleses da Faculdade de Letras da Universidade do Porto, 1988, pp. 221-240. LALANDA, Maria Margarida – “A política externa de D. Afonso IV (1325-1357)”. Arquipélago. História [Em linha] 11 (1989), pp. 107-151. [Consultado a 12 julho 2018]. Disponível em https://repositorio.uac.pt/bitstream/10400.3/982/1/MariaMargaridaNogueiraLalanda_p107-151.pdf. LAZZARINI, Isabella – Communication and Conflict. Italian Diplomacy in the Early Renaissance, 1350-1520. Oxford: Oxford University Press, 2015. LEROY, Béatrice – Du France parler en politique. Aimer et devoir écrire aux souverains en Castille au XVe siècle. Limoges: Université de Limoges/Pulim, 2014. LIMA, Douglas Mota Xavier de - “A política matrimonial de D. João I: um instrumento de afirmação dinástica. Portugal, 1387-1430”. Roda da Fortuna. Revista Eletrônica sobre Antiguidade e Medievo 3/2 (2014), pp. 191-209. LIMA, Douglas Mota Xavier de - “Novos olhares sobre a diplomacia medieva”. Revista Transversos 3 (2015), pp. 77-91. LIMA, Douglas Mota Xavier de - A diplomacia portuguesa no reinado de D. Afonso V (1448-1481). Niterói: Universidade Federal Fluminense, 2016. Tese de Doutoramento. LIMA, Douglas Mota Xavier de - “Regal ceremonies and diplomatic practices. Contributions from the travel narratives from the 15th century”. in VIGIL MONTES, Néstor (dir.) - Comunicación política y diplomacia en la Baja Edad Media [Em linha]. Évora: Publicações do Cidehus, 2019 [Consultado a 1 julho 2019]. Disponível em https://books.openedition.org/cidehus/7453. LOPES, Paulo – Um agente português na Roma do Renascimento. Lisboa: Temas e Debates/Círculo de Leitores, 2013. MACEDO, Jorge Borges de – História Diplomática Portuguesa. Constantes e linhas de força. Estudo de Geopolítica. 2ª. Ed. Lisboa: Tribuna/Instituto da Defesa Nacional, 2006. MAGALHÃES, José Calvet de  – A Diplomacia Pura. Lisboa: Bizâncio, 2005. MARINHO, Duarte de Babo - “A ação diplomática de Pedro Gonçalves de Malafaia na libertação do infante D. Pedro de Aragão (1432): antecedentes e significados”. Revista Portuguesa de História, [Em Linha] 46 (2015), pp. 83-96. [Consultado a 12 julho 2018]. Disponível em https://digitalis-dsp.uc.pt/bitstream/10316.2/38184/1/A%20acao%20diplomatica%20de%20Pedro%20Goncalves%20de%20Malafaia.pdf?ln=pt-pt. MARINHO, Duarte de Babo – Os embaixadores portugueses nos reinos ibéricos (1431-1474). Um estudo sociodemográfico. 2 vols. Porto: Faculdade de Letras da Universidade do Porto, 2017. Tese de Doutoramento. MARINHO, Duarte de Babo – “Os agentes diplomáticos da Baixa Idade Média portuguesa (1431-1474): uma elite ao serviço da Coroa”. História: Revista da Faculdade de Letras da Universidade do Porto [Em linha] 7/2 (2017), pp. 10-30. [Consultado a 12 julho 2018]. Disponível em https://ler.letras.up.pt/uploads/ficheiros/16032.pdf. MARINHO, Duarte Babo – “Diplomacia visual na Baixa Idade Média portuguesa: os oficiais de armas”. Medievalista [Em linha] 24 (julho-dezembro 2018) [Consultado a 12 julho 2018]. Disponível em http://www2.fcsh.unl.pt/iem/medievalista/MEDIEVALISTA24/marinho2404.html MARINHO, Duarte de Babo – “A atuação diplomática de Gomes Eanes e de Martim de Távora com vista à libertação do Infante D. Fernando (1439-1441)”. Revista Mátria Digital 6 (2018), pp. 155-185. MARINHO, Duarte de Babo – “Recensão de Diplomatie et «Relations Internationales» au Moyen Âge (IXe-XVe siècle)”. História: Revista da Faculdade de Letras da Universidade do Porto [Em linha] 9/1 (2019), pp. 235-238. [Consultado a 1 julho 2019]. Disponível em https://ojs.letras.up.pt/index.php/historia/article/view/6167/5809. MARINHO, Duarte de Babo. COSTA, Paula Pinto. MARIA CRISTINA, Cunha – “Preparation of embassies and protocol followed by royal Portuguese ambassadors in late-medieval times”. E-Journal of Portuguese History [Em linha] 1/17 (2019). [Consultado a 1 julho 2019]. Disponível em https://www.brown.edu/Departments/Portuguese_Brazilian_Studies/ejph/forth.html. MARINHO, Duarte de Babo - “Diplomacia e espionagem na baixa Idade Média portuguesa”. in VIGIL MONTES, Néstor (dir.) - Comunicación política y diplomacia en la Baja Edad Media [Em linha]. Évora: Publicações do Cidehus, 2019 [Consultado a 1 julho 2019]. Disponível em https://books.openedition.org/cidehus/6946. MATTINGLY, Garrett – Renaissance Diplomacy. Baltimore: Penguin Books, 1964. MENDONÇA, Manuela – “Diplomatas portugueses na costa africana (1434-1495: uma releitura de João de Barros)”. Mare Liberam: revista de história dos mares 10 (1995), pp. 341-353. MENDONÇA, Manuela – “Portugal na Christiana Respublica”. in SOARES, Nair de Nazaré Castro; LÓPEZ MOREDA, Santiago – Génese e consolidação da Ideia de Europa. Idade Média e Renascimento. Vol. 4. Coimbra: Imprensa da Universidade de Coimbra, 2009, pp. 61-82. MIRANDA, Flávio – Portugal ant the Medieval Atlantic. Commercial Diplomacy, Merchants, and Trade, 1143-1488. Porto: Faculdade de Letras da Universidade do Porto, 2012. Tese de Doutoramento. MOEGLIN, Jean-Marie e PÉQUIGNOT, Stéphane (dir.) – Diplomatie et «Relations Internationales» au Moyen Âge (Ixe-XVe siècle). Paris, Press Universitaires de France, 2017. MONTEIRO, Nuno Gonçalo; CARDIM, Pedro – “La Diplomacia durante el Antiguo Régimen. Perfil sociológico y trayectorias”. Cuadernos de Historia Moderna [Em linha] 30 (2005), pp. 7-40. [Consultado a 12 julho 2018]. Disponível em https://revistas.ucm.es/index.php/CHMO/article/view/CHMO0505110007A/22171. MORENO, Humberto Baquero – “O papel da diplomacia portuguesa no Tratado de Tordesilhas”. Revista da Faculdade de Letras. História [Em linha] 12 (1995), pp. 135-150. [Consultado a 12 julho 2018]. Disponível em https://repositorio-aberto.up.pt/bitstream/10216/7845/2/2025.pdf. MOTA, Eugénia Pereira da – Do Africano ao Príncipe Perfeito: (1480-1483). Caminhos da burocracia régia. Vol. 1. Porto: Faculdade de Letras da Universidade do Porto, 1989. Dissertação de Mestrado. NIETO SORIA, José́ Manuel – Iglesia y génesis del Estado Moderno en Castilla (1369-1480). Madrid: Editorial Complutense, 1993. NOGALES RINCÓN, David – “La cultura del pacto en las relaciones diplomáticas luso- castellanas durante el periodo Trastámara (1369-1504)”. En la España medieval [Em linha] 35 (2012), pp. 121-144. [Consultado a 12 julho 2018]. Disponível em https://dialnet.unirioja.es/servlet/articulo?codigo=3986849. OCHOA BRUN, Miguel Ángel – “Los usos diplomáticos en la época del Tratato de Tordesillas”. in El Tratado de Tordesillas y sy Época. Congreso Internacional de Historia. Vol. 2. Junta de Castilla y León, 1995, pp. 801-824. OLIVERA SERRANO, Cesar – “Servicio al rey y diplomacia castellana: Don Juan Manuel de Villena (1462)”. Anuario de Estudios Medievales, [Em linha] 25 (1995), pp. 463-488. [Consultado a 12 julho 2018]. Disponível em http://digital.csic.es/bitstream/10261/17263/1/20090717140926228.pdf. PÉQUIGNOT, Stéphane – “Les diplomaties occidentales, XIIIe-XVe siècles, dans les relations diplomatiques au Moyen Âge”. In Formes et enjeux. Paris: Publications de la Sorbonne, 2011, pp. 47-66. PÉQUIGNOT, Stéphane – “Les instructions aux ambassadeurs des rois d’Aragon (XIII- XV siècles). Jalons pour l'histoire de la fabrique d'une parole royale efficace”. Cahiers d’études hispaniques médiévales 31 (2008), pp. 17-43. PÉQUIGNOT, Stéphane – Au nom du roi. Pratique diplomatique et pouvoir durant le règne de Jacques II d’Aragon (1291-1327). Madrid: Bibliothèque de la Casa Velázquez, 2009. RAMIREZ VAQUERO, Eloísa – “Estrategias diplomáticas de rey de Navarra en el tránsito al siglo XV. in XXXI Semana de Estudios Medievales. Pamplona: Gobierno de Navarra/Departamento de Cultura y Turismo/Institución Príncipe de Viana, 2005, pp. 373-421. RAMOS, Manuel – Orationes de Jean Jouffroy em favor do Infante D. Pedro (1449- 1450). Retórica e Humanismo cívico. Porto: Faculdade de Letras da Universidade do Porto, 2006. Tese de Doutoramento. RODRIGUES, Ana Maria S. A. – “Casamentos régios na Idade Média: um feixe de problemas”. in RODRIGUES, Ana Maria S. A.; SILVA, Manuela Santos; FARIA, Ana Leal de (coord.) – Casamentos da Família Real Portuguesa. Vol. 1. Lisboa: Círculo de Leitores, 2017, pp. 35-56. RUSSELL, Peter – A intervenção inglesa na Península Ibérica durante a Guerra dos Cem Anos. Lisboa: Imprensa Nacional da Casa da Moeda, 2000. SANTOS, Maria Alice – A sociologia da representação político-diplomática no Portugal de D. João I. Lisboa: Universidade Aberta, 2015. Tese de Doutoramento. SOUSA, Armindo de – As cortes medievais portuguesas: 1385-1490. 2 vols. Porto: INIC, 1990. VAZ, Vasco Rodrigo dos Santos Machado – A boa memória do monarca. Os escrivães da Chancelaria de D. João I (1395-1433). Vol. 1. Porto: Faculdade de Letras da Universidade do Porto. 1995. Dissertação de Mestrado. VIGIL MONTES, Néstor – “«Tractados de pazes, aliança e concordia entre as duas coroas de Portugal e Inglaterra», un cartulario realizado a comienzos del siglo XV para consolidar el Tratado de Windsor entre los reinos de Inglaterra y Portugal (1386), la alianza permanente más prolongada de la historia”. Espacio, Tiempo y Forma. Revista de la Facultad de Geografía e Historia [Em linha] 32 (2019), pp. 469-498. [Consultado a 1 julho 2019]. Disponível em http://revistas.uned.es/index.php/ETFIII/article/view/22403/19166. VIGIL MONTES, Néstor – "El rumor político en diplomacia: la especulación sobre el posible destino de la armada portuguesa que se estaba preparando para finalmente conquistar Ceuta (1411-1415)”. in VILLARROEL GONZÁLEZ, Óscar, GARCÍA ISAAC, José Marcos, y CHELLE ORTEGA, José Antonio (eds.) - Guerra y Diplomacia en la Península Ibérica (1369-1474). Madrid: La Ergástula, 2019, pp. 15-40. VIGIL MONTES, Néstor – “Diplomacia y diplomática: un análisis de las fuentes documentales de la diplomacia bajomedieval”. in VIGIL MONTES, Néstor (dir.) - Comunicación política y diplomacia en la Baja Edad Media [Em linha]. Évora: Publicações do Cidehus, 2019. [Consultado a 1 julho 2019]. Disponível em https://books.openedition.org/cidehus/6880. VIGIL MONTES, Néstor – “A modo de introducción: nuevos caminos de la historiografía sobre la diplomacia medieval”. in Comunicación política y diplomacia en la Baja Edad Media. Dir. Néstor Vigil Montes. Évora: Publicações do Cidehus, 2019. [Consultado a 1 julho 2019]. Disponível em https://books.openedition.org/cidehus/7438. VILLANUEVA MORTE, Concepción – “La correspondencia diplomática entre los embajadores del ducado de Milán y la corte de los reinos hispánicos en la segunda mitad del siglo XV”. in Dossier la sociedad cortesana en la Península Ibérica (siglos XIV-XV): fuentes para su estudio. Madrid: Bibliothèque de la Casa Velázquez, 2015, pp. 143-166. WATKINS, John – “Toward a New Diplomatic History of Medieval and Early Modern Europe”. Journal of Medieval and Early Modern Studies [Em linha] 38/1 (2008), pp. 1-14. [Consultado a 8 outubro 2019]. Disponível em https://read.dukeupress.edu/jmems/issue/38/1.